Challenges in Designing Learning Media among Mathematics Education Students - Salsabila, Nilza Humaira; Novitasari, Dwi; Triutami, Tabita Wahyu; Lu’luilmaknun, Ulfa; Kertiyani, Ni Made Intan; Oktavihari, Dita (FKIP Universitas Mataram, 2025)
This study aims to describe the challenges or difficulties faced by mathematics education students in designing learning media, especially student worksheet, interactive presentation slides, and educational video. This research is a quantitative descriptive research with the subjects in this study are 4th semester students enrolled in the Mathematics Learning Technology course, as many as 23. Data collection was carried out through distributing questionnaires to students regarding their difficulties in developing media. The results showed that students experienced the most difficulties in developing educational videos compared to student worksheet, interactive presentation slides. The main difficulties in educational videos include technical skills such as editing, flow design, and application usage.